Financial Transparency and Accountability In Nonprofit Organizations A Systematic Literature Review - Nurdiani, Tina; Rahmawati, Desi; Pogo, Tajuddin; Bakar, Noor Raudhiah Binti Abu (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
Nonprofit organizations (NPOs) play a crucial role in societal development. However, achieving financial transparency and accountability remains a persistent challenge. This study systematically analyzes global research trends, emerging themes, and financial transparency and accountability gaps within NPOs from 2015 to 2024. Using a Systematic Literature Review (SLR) with the PRISMA-P approach, data were extracted from peer-reviewed articles in the Scopus database, with thematic analysis and bibliometric tools, such as VOSviewer, employed for synthesis. Findings reveal the transformative potential of digital tools, such as blockchain and social media, in enhancing real-time transparency while also highlighting structural and contextual barriers to their implementation. Key recommendations include fostering board diversity, professionalization, and cross-sector collaboration to strengthen governance frameworks. Despite advancements, regional disparities in technological adoption and underexplored cultural contexts present opportunities for future research. This study contributes to academic discourse and evidence-based practices, empowering NPOs, regulators, and donors to effectively address evolving transparency demands.